Transforming Accounting System With Blockchain Technology Implementation - Fitriani, Ajeng Pipit (Etihad: Journal of Islamic Banking and Finance, 2024)
Introduction: The increasing need for transparency and accountability in financial reporting has highlighted significant shortcomings in traditional accounting systems, particularly data manipulation and fraud. This research explores the potential of blockchain technology, a decentralized ledger introduced through Bitcoin, as a transformative solution to these issues. Research Methods: This study uses a qualitative descriptive design because this study describes the details and interprets the initial data, symptoms and phenomena obtained during the study. This study is a qualitative study using a library research approach. Results: The findings demonstrate that blockchain can significantly improve data reliability through its key features, including immutability, decentralization, transparency, and enhanced security. Furthermore, blockchain offers operational efficiencies in financial reporting, mainly through transaction automation, real-time auditability, and cost reduction. Conclusion: This study finds that Blockchain provides data reliability assurance through an immutable and distributed system, minimizing the risk of data manipulation or fraud.